Aspects on the perception of young people regarding balneotherapy tourism in Romania - Aurelia-Felicia STĂNCIOIU (Theoretical and Applied Economics, 2013)

(untitled)
The delimitation of perceptions regarding balneotherapy destinations is a defining process for shaping their positioning in consumers’ minds. Therefore, creating how balneotherapy tourism products specific activities are perceived by consumers and the relationship that they have reported to the sensations that assemble the touristic experience is essential in creating a tourism image. In this sense, a quantitative marketing research was conducted on a sample of 573 young people undergoing university studies in order to know their perception regarding balneotherapy resorts in Romania, analyzing the importance and particularities of each sensation in relation to balneotherapy resorts felt by respondents that differentiate the balneotherapy experience from other touristic experiences.